1930
DOI: 10.1021/ie50243a017
|View full text |Cite
|
Sign up to set email alerts
|

The Cooking Process I—Role of Water in the Cooking of Wood1

Abstract: degree of accuracy as obtainable when applied to the ordinary run of absorption oils or naphthas. Indications of inconsistent deviations from Raoult's law in previous investigations can be explained by the fact that the compo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1931
1931
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The unsaturated compounds, which were easily polymerized, were being created by the elimination of carboxyl and hydroxyl groups [123]. In the case of (highly reactive) lignin fragments, polymerization has been reported to be completed within several minutes above 300 °C [232,233]. Falco et al [234] stated that this co-condensation could be strengthened by increasing the amount of monosaccharide glucose when synthesized the nitrogen-doped carbon materials from the microalgae by the HT.…”
Section: Denitrificationmentioning
confidence: 99%
“…The unsaturated compounds, which were easily polymerized, were being created by the elimination of carboxyl and hydroxyl groups [123]. In the case of (highly reactive) lignin fragments, polymerization has been reported to be completed within several minutes above 300 °C [232,233]. Falco et al [234] stated that this co-condensation could be strengthened by increasing the amount of monosaccharide glucose when synthesized the nitrogen-doped carbon materials from the microalgae by the HT.…”
Section: Denitrificationmentioning
confidence: 99%
“…It has been reported by several authors (1)(2)(3)(4)(5)(6) that by autocatalysed hydrolysis (autohydrolysis) of wood, the lignin is modified in such a way that it can be partially extracted in a second stage at low temperatures using certain organic solvents or dilute aqueous alkalies. Earlier work at this laboratory (7)(8)(9)(10) has shown that at any given temperature there is a characteristic autohydrolysis time for maximum lignin extractability.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been already proposed (Aronovsky and Gortner, 1930), this phenomenon can be related to a structural change of lignin, i.e., depolymerization. As it has been already proposed (Aronovsky and Gortner, 1930), this phenomenon can be related to a structural change of lignin, i.e., depolymerization.…”
Section: Analysis Of the Data Inmentioning
confidence: 70%
“…; handsheet, made at 70 g/mZ. has been found to enhance alkali solubility and further degradation of cellulose (Binger and Norman, 1957). On the other hand, because of prehydrolysis, a significant economy in the amount of alkali needed for delignification is possible (cf.…”
Section: Analysis Of the Data Inmentioning
confidence: 99%